Toxicity mechanism of acrolein on DNA damage and apoptosis in BEAS-2B cells: Insights from cell biology and molecular docking analyses. (30th January 2022) - Liu, Dan; Cheng, Ye; Tang, Zhipeng; Mei, Xueying; Cao, Xiangyu; Liu, Jianli
Highlights: Acrolein induced DNA damage and nucleus condensation in BEAS-2B cells. Acrolein activated DNA damage response, and caused cell cycle arrest in G2/M phase. The spontaneous binding of acrolein with DNA was revealed by molecular docking. Acrolein induced BEAS-2B cell apoptosis by the mitochondrial apoptotic pathway. Abstract: Acrolein is a hazardous air pollutant for humans and is responsible for many pulmonary diseases, but the underlying mechanisms have not been completely elucidated. This work is focused on the genotoxicity effects of human bronchial epithelial (BEAS-2B) cells induced by acrolein (20, 40, 80 μM). The molecular mechanism was investigated base on DNA damage and mitochondrial apoptosis pathways. The results showed that after exposure to acrolein, the cell viability, glutathione (GSH) of BEAS-2B cells were reduced. Reactive oxygen species (ROS) level significantly increased, accompanied by increased levels of DNA damage-related indicators 8-hydroxy-2 deoxyguanosine (8−OHdG), DNA content of comet tail (Tail DNA%), olive tail moment (OTM), and nucleus morphology. Cell arrested at the G2/M phase. Then, the DNA damage response (DDR) signaling pathway (Ataxia-telangiectasia-mutated (ATM) and Rad-3-related (ATR)/Chk1 and ATM/Chk2) and the consequent cell cycle checkpoints were activated. The expression of γ-H2AX was significantly increased, indicating that acrolein induced DNA double-strand breaks. Molecular docking assay showed that acrolein bound to DNA in a spontaneous process. Moreover, mitochondrial apoptosis pathway involved in apoptosis, mitochondrial membrane potential (MMP) and adenosine triphosphate (ATP) content of BEAS-2B cells were significantly reduced, and the apoptosis rate was significantly increased. The protein expression of Bax/Bcl-2 and Cleaved Caspase-3 were increased, and JNK signaling pathway was activated. All the results indicated that acrolein induced DNA damage, activated DDR and mitochondrial apoptosis pathways, which might be the pivotal factors to mediate cytotoxicity in BEAS-2B cells.